2017
DOI: 10.4274/jtgga.2016.0138
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical data and human papilloma virus genotype influence spontaneous regression in grade I cervical intraepithelial neoplasia?

Abstract: Objective:To determine whether medical history, clinical examination and human papilloma virus (HPV) genotype influence spontaneous regression in cervical intraepithelial neoplasia grade I (CIN-I).Material and Methods:We retrospectively evaluated 232 women who were histologically diagnosed as have CIN-I by means of Kaplan-Meier curves, the pattern of spontaneous regression according to the medical history, clinical examination, and HPV genotype.Results:Spontaneous regression occurred in most patients and was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In his study Cortes found spontaneus regression of LSIL in 50% and progresion in HSIL in 6% in the 2-year follow-up. Other authors found regresion of LSIL in 57%, persistance in 32% and progresion in HSIL in 11% ( 21 , 22 , 23 ). Our analysis showed that the regression frequency was significantly lower (p<0,05) in women who had follow-up (28,9%), comparing with the group of women with cryotherapy (87,3%).…”
Section: Discussionmentioning
confidence: 86%
“…In his study Cortes found spontaneus regression of LSIL in 50% and progresion in HSIL in 6% in the 2-year follow-up. Other authors found regresion of LSIL in 57%, persistance in 32% and progresion in HSIL in 11% ( 21 , 22 , 23 ). Our analysis showed that the regression frequency was significantly lower (p<0,05) in women who had follow-up (28,9%), comparing with the group of women with cryotherapy (87,3%).…”
Section: Discussionmentioning
confidence: 86%
“…This resulted in 125 studies being excluded. The remaining 89 studies were included for meta-analysis, of which 63 studies with CIN 1 patients, 8–70 42 studies with CIN 2 patients, 11,26,27,35–37,39,41–44,50,52,53,57,69–95 and 7 studies with CIN 3 patients 3,26,41,72,81,83,88 . The characteristics and the follow-up protocol of the included studies are summarized in Supplementary Tables 1–3, http://links.lww.com/LGT/A239, http://links.lww.com/LGT/A240, http://links.lww.com/LGT/A241.…”
Section: Resultsmentioning
confidence: 99%
“…Results with a somewhat bigger percentage of progression were found by Barken, who states that 13% to 16% of untreated LSIL progresses into cervical carcinoma ( 12 ). Regression of HPV infection can occur spontaneously, but in 10-20% of women that infection persists and these women have a risk of developing LSIL, HSIL or cervical carcinoma ( 13 ). Monitoring data of untreated ASCUS and LSIL lesions state that LSIL regresses in 28.9%, and ASCUS in 29.8%.…”
Section: Discussionmentioning
confidence: 99%